Analisis Persepsi Nasabah Terhadap Produk Tabungan Perencanaan Berjangka Syariah (TAPENAS) di BSI KCP Jepara - Alfiyah, Qodriyatul; Ansori, Miswan; Mubarok, Ahmad Fauzan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The Sharia Term Savings Planning (Tapenas) product is a term savings service that helps customers prepare for future financial needs based on sharia principles. This study aims to analyze customer perceptions of the Tapenas product at BSI KCP Jepara and identify factors that influence these perceptions. This study uses a qualitative descriptive approach with a field research method. Data were collected through interviews, observations, and documentation of informants selected using a purposive sampling technique. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that customers have a positive perception of the Tapenas product because it is considered to support long-term financial planning, provide a sense of security in fund management, and is in accordance with sharia principles. This perception is influenced by customer knowledge of the product, service quality, promotions, user experience, and level of trust in the bank. These findings suggest that strengthening product education and more informative marketing communications are needed to increase public understanding and interest in sharia-based term savings products